CO2 gasification in a dual fluidized bed reactor system: Impact on the product gas composition. (1st October 2019) - Mauerhofer, A.M.; Fuchs, J.; Müller, S.; Benedikt, F.; Schmid, J.C.; Hofbauer, H.
Highlights: 100 kWth dual fluidized bed CO2 /steam gasification at TU Wien. Shift of product gas composition to higher CO contents and lower H2 contents. Decrease of H2 /CO ratio compared to pure steam gasification. Lower tar contents for CO2 /steam gasification compared to pure steam gasification. No significant reduction of tar when limestone was added. Abstract: The use of CO2 as gasification agent in the 100 kWth dual fluidized bed gasification pilot plant was investigated at TU Wien. For this purpose, steam was replaced stepwise by CO2 as gasification agent. Softwood was used as fuel and olivine as bed material. Starting from 100 vol.-% steam as gasification agent, substituting it by 32, 45 and finally 68 vol.-% CO2 . All loop seals were fluidized further with steam, which resulted in these volume percentages. Additionally, a CO2 gasification test campaign converting softwood with a mixture (90/10 wt.-%) of olivine and limestone was investigated. For this case, the gasification agent was composed of 65 vol.-% CO2 and 35 vol.-% steam. The use of CO2 as gasification agent led to changes of the product gas. Instead of a H2 -enriched product gas, which was produced during steam gasification, CO and CO2 occupied the major share of the product gas. Consequently, the H2 /CO ratios as well as the lower heating values decreased when substituting steam by CO2 . Tar contents were lower for CO2 /steam gasification compared to pure steam gasification.